Quality Improvements in Public Livestock Services Delivery: Are Farmers Ready to Pay? An Inquiry in South India - Kathiravan, G.; Thirunavukkarasu, M. (Journal of Buffalo Science, 2013)
Farmers Willingness To Pay (WTP) for improving the quality of public livestock services delivery, in terms of Service Provider and Farmer Relationship (SPFR), chance of recovery from ailments and chance of conception following Artificial Insemination (AI), was assessed through Contingent Valuation (CV) in southern peninsular state of India, the Tamil Nadu State. The districts of the state were categorized as ‘Livestock Developed’ (LD) and ‘Livestock Under Developed’ (LUD) based on initial base line developed. Contingent Valuation (CV) approach and Tobit regressions were used to assess variations in the stated Willingness To Pay (WTP) values, and the probability of stating a positive WTP value for respondents who declared that they were not willing to pay. Overall, the respondents in the study area were willing to pay INR 3.91 for improving the SPFR attribute of the public veterinary centre, while they were ready to pay INR 5.84 for augmenting the chances of recovery from illness by the services of public veterinary centres. In order to benefit from improved chance of conception of their bovines after AI, the farmers were willing to pay INR 11.71. An absolute concordance on the levels of attributes and the variations in the stated positive WTP values for quality improvements was noticed. Tobit regression analyses on the improvements of all above attributes indicated that the farmers who were at disadvantaged levels of an attribute were willing to pay more compared to those at an advantaged level.